﻿À propos d’un fragment de lécythe grec à Québec - De Haître Ford, Micheline (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 1988)
Funerary lekythos were placed in graves in Greek cemeteries. The use of such huge marble vases as funerary monuments appeared in Greece by the middle of the fifth century and became fashionable until 317 b.c. Lekythos were decorated with paintings or with carved reliefs. The figure of the deceased was represented alone or with his family. The representation often included an inscription and sometimes the figures were identified with their names.A fragment of one of these lekythos at Laval University represents a farewell scene in low-relief. The author discusses the meaning of the representation, the usual shaking-hands gesture of the figures. Comparisons with dated, better-known funerary lekythos enable the author to propose a date for the Quebec fragment.